DIALECTIC REGARDING THE MEANING OF ABORTUS PROVOCATEUR ON THE CRIME OF RAPE VICTIMS - Ndaru Satrio; Wiend Sakti Myharto; Muhammad Syaiful Anwar (Universitas Lampung, 2022)
Legalizing abortion for rape victims creates a debate in substance and the application of the theories and principles surrounding it. The author tries to see the meaning from two different sides, namely, from the interests of protecting rape victims and the interests of the children conceived by rape victims. The method used by the author is a normative juridical approach. The meaning contained in abortion provocations from the point of view of a rape victim is protection for the victim. This protection is certainly carried out from the effects or impacts of the actions of the perpetrators of rape. Meanwhile, the meaning contained in abortion provocateurs from the point of view of Human Rights (HAM) leads to the fulfillment of the fetus's right to life mentioned in the previous description, which is called a child who is still in the womb. The author provides suggestions as solutions to problems that may arise, including: (1) the need for synchronization and harmonization of existing regulations, in this case between regulations on health and regulations on human rights; (2) legislators must prioritize higher interests in the event of a similar situation. According to the author, the human rights interests of children in the womb must be prioritized.